Durvalumab alone and durvalumab plus tremelimumab versus chemotherapy in previously untreated patients with unresectable, locally advanced or metastatic urothelial carcinoma (DANUBE): a randomised, open-label, multicentre, phase 3 trial. Issue 12 (December 2020) - Powles, Thomas; van der Heijden, Michiel S; Castellano, Daniel; Galsky, Matthew D; Loriot, Yohann; Petrylak, Daniel P; Ogawa, Osamu; Park, Se Hoon; Lee, Jae-Lyun; De Giorgi, Ugo; Bögemann, Martin; Bamias, Aristotelis; et al.
Summary: Background: Survival outcomes are poor for patients with metastatic urothelial carcinoma who receive standard, first-line, platinum-based chemotherapy. We assessed the overall survival of patients who received durvalumab (a PD-L1 inhibitor), with or without tremelimumab (a CTLA-4 inhibitor), as a first-line treatment for metastatic urothelial carcinoma. Methods: DANUBE is an open-label, randomised, controlled, phase 3 trial in patients with untreated, unresectable, locally advanced or metastatic urothelial carcinoma, conducted at 224 academic research centres, hospitals, and oncology clinics in 23 countries. Eligible patients were aged 18 years or older with an Eastern Cooperative Oncology Group performance status of 0 or 1. We randomly assigned patients (1:1:1) to receive durvalumab monotherapy (1500 mg) administered intravenously every 4 weeks; durvalumab (1500 mg) plus tremelimumab (75 mg) administered intravenously every 4 weeks for up to four doses, followed by durvalumab maintenance (1500 mg) every 4 weeks; or standard-of-care chemotherapy (gemcitabine plus cisplatin or gemcitabine plus carboplatin, depending on cisplatin eligibility) administered intravenously for up to six cycles. Randomisation was done through an interactive voice–web response system, with stratification by cisplatin eligibility, PD-L1 status, and presence or absence of liver metastases, lung metastases, or both. The coprimary endpoints were overall survival compared between the durvalumab monotherapy versus chemotherapy groups in the population of patients with high PD-L1 expression (the high PD-L1 population) and between the durvalumab plus tremelimumab versus chemotherapy groups in the intention-to-treat population (all randomly assigned patients). The study has completed enrolment and the final analysis of overall survival is reported. The trial is registered with ClinicalTrials.gov, NCT02516241, and the EU Clinical Trials Register, EudraCT number 2015-001633-24. Findings: Between Nov 24, 2015, and March 21, 2017, we randomly assigned 1032 patients to receive durvalumab (n=346), durvalumab plus tremelimumab (n=342), or chemotherapy (n=344). At data cutoff (Jan 27, 2020), median follow-up for survival was 41·2 months (IQR 37·9–43·2) for all patients. In the high PD-L1 population, median overall survival was 14·4 months (95% CI 10·4–17·3) in the durvalumab monotherapy group (n=209) versus 12·1 months (10·4–15·0) in the chemotherapy group (n=207; hazard ratio 0·89, 95% CI 0·71–1·11; p=0·30). In the intention-to-treat population, median overall survival was 15·1 months (13·1–18·0) in the durvalumab plus tremelimumab group versus 12·1 months (10·9–14·0) in the chemotherapy group (0·85, 95% CI 0·72–1·02; p=0·075). In the safety population, grade 3 or 4 treatment-related adverse events occurred in 47 (14%) of 345 patients in the durvalumab group, 93 (27%) of 340 patients in the durvalumab plus tremelimumab group, and in 188 (60%) of 313 patients in the chemotherapy group. The most common grade 3 or 4 treatment-related adverse event was increased lipase in the durvalumab group (seven [2%] of 345 patients) and in the durvalumab plus tremelimumab group (16 [5%] of 340 patients), and neutropenia in the chemotherapy group (66 [21%] of 313 patients). Serious treatment-related adverse events occurred in 30 (9%) of 345 patients in the durvalumab group, 78 (23%) of 340 patients in the durvalumab plus tremelimumab group, and 50 (16%) of 313 patients in the chemotherapy group. Deaths due to study drug toxicity were reported in two (1%) patients in the durvalumab group (acute hepatic failure and hepatitis), two (1%) patients in the durvalumab plus tremelimumab group (septic shock and pneumonitis), and one (<1%) patient in the chemotherapy group (acute kidney injury). Interpretation: This study did not meet either of its coprimary endpoints. Further research to identify the patients with previously untreated metastatic urothelial carcinoma who benefit from treatment with immune checkpoint inhibitors, either alone or in combination regimens, is warranted. Funding: AstraZeneca.